Comprehensive investigation of green-Saponin as surfactant: Assessing the influence of surfactant’s salinity, concentration, pH, extraction methods, and core flooding simulation on surfactant flooding - Nur Najwa Syuhada, Suhaidi; Maryam Jameelah, Hussin; Hazwan Mahiruddin, Hashim; Rahimah, Embong; Norasyikin, Ismail (AIP Publishing, 2025)
Surfactant flooding is one of the methods in chemical flooding for enhanced oil recovery (EOR). Surfactant flooding aims to reduce the interfacial tension (IFT) between oil and water by injecting surfactant into wells. However, this method has been a setback for the industry as most surfactants used are chemical surfactants that are highly toxic, non-unsustainable practices and expensive. Thus, researchers have been researching green surfactants made from plants, microorganisms, and waste to achieve a sustainable solution for EOR use. This paper will summarize and evaluate the development and validation of saponin from Nephelium lappaceum for surfactant flooding and its application using T-Navigator software. This paper will assess the influence of salinity, concentration, and pH on surfactants. Additionally, it will discuss the extraction method used for saponin and its application in core flooding simulation. The findings of this review have the potential to significantly impact the EOR technique, specifically the surfactant flooding.